Tubewell transfer in Gujarat: a study of the GWRDC approach - Mukherji, Aditi; Kishore, Avinash (International Water Management Institute, 2003)
In India public (government) tubewells were built with the intention of providing irrigation to all categories of farmers in a fair, equitable and affordable manner. However, most public tubewell programs across India have failed on all these counts. Efforts to transfer their management to water users too have met with little success. Nonetheless, the Gujarat Water Resources Development Corporation (GWRDC)-a state-owned public company-has achieved rare success in tubewell transfer by handing over management of around 60 percent of public tubewells in the Gujarat state to user groups. This study tries to identify the factors that helped in accelerating the transfer process and evaluate the performance of transferred tubewells against those owned by individuals and GWRDC. It also suggests some policy changes that can make the scheme function better and explores the replicability of the success achieved in Gujarat.